Development of Pavement Roughness Model and Maintenance Priority Index for Kerala State Highway I - Minu P K and Sreedevi B G (International Journal of Engineering Research & Technology (IJERT), 2014)
The present study developed a Maintenance Priority Index (MPI) for the six sections of the State Highway (SH-1) using certain factors affecting pavement maintenance. The factors considered in this study were pavement condition, riding quality, traffic characteristics, land use characteristics and characteristic deflection of the pavement. A relationship between pavement roughness and distress parameters like area of ravelling, cracked area etc. also developed. The pavement distress data was collected on SH stretching from Vetturoad to Adoor. Roughness survey was conducted using Bump integrator and Benkelman beam was used for the measurement of deflections in the pavement. Pavement Condition Indexes (PCI) for each section was determined. The relation between pavement distress and pavement roughness was modelled using Multiple Linear Regression (MLR) analysis. The models were significant as the forecasting errors were within the limits.